Navigating the Trauma of Change - Kent Crookston (Academic Chairpersons Conference Proceedings, 2018)
In a recent national survey, academic leaders identifies “dealing with change as their second topmost concern. Crookston has researched, and interacted first-hand with the “change characters” that emerge from within any group faced with restructuring or innovation. Participants leave this workshop better able to anticipate, understand, and work effectively with the range of personalities that react and adapt differently to change.
Keywords: Navigating Trauma Change Chair Leadership Transition